HISTORY OF INDIAN TRADITIONAL MEDICINE: A MEDICAL INHERITANCE. - Adhikari, Partha Pradip; Paul, Satya Bhusan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Indian Traditional Medicine, the foundation of age-old practice of medicine in the world, has played an essential role in human health care service and welfare from its inception. Likewise, all traditional medicines are of its own regional effects and dominant in the West Asian nations; India, Pakistan, Tibet, and so forth, East Asian nations; China, Korea, Japan, Vietnam, and so forth, Africa, South and Central America. This article is an attempt to illuminate Indian traditional medical service and its importance, based on recent methodical reviews. Methods: Web search engines for example; Google, Science Direct and Google Scholar were employed for reviews as well as for meta-analysis. Results: There is a long running debate between individuals, who utilize Indian Traditional Medicines for different ailments and disorders, and the individuals who depend on the present day; modern medicine for cure. The civil argument between modern medicine and traditional medicines comes down to a basic truth; each person, regardless of education or sickness, ought to be educated about the actualities concerning their illness and the associated side effects of medicines. Therapeutic knowledge of Indian traditional medicine has propelled various traditional approaches with similar or different theories and methodologies, which are of regional significance. Conclusion: To extend research exercises on Indian Traditional Medicine, in near future, and to explore the phytochemicals; the current review will help the investigators involved in traditional medicinal pursuit.